Promoting Healthy Food Access and Nutrition in Primary Care: A Systematic Scoping Review of Food Prescription Programs. Issue 3 (March 2022) - Little, Matthew; Rosa, Ebony; Heasley, Cole; Asif, Aiza; Dodd, Warren; Richter, Abby
Objective: To conduct a scoping review to synthesize evidence on food prescription programs. Data Source: A systematic search of PubMed, CINAHL, Web of Science, Embase, and the Cochrane Library was conducted using key words related to setting, interventions, and outcomes. Study Inclusion and Exclusion Criteria: Publications were eligible if they reported food prescription administered by a health care practitioner (HCP) with the explicit aim of improving healthy food access and consumption, food security (FS), or health. Data Extraction: A data charting form was used to extract relevant details on intervention characteristics, study methodology, and key findings. Data Synthesis: Study and intervention characteristics were summarized. We undertook a thematic analysis to identify and report on themes. A critical appraisal of study quality was conducted using the Mixed Methods Appraisal Tool (MMAT). Results: A total of 6145 abstracts were screened and 23 manuscripts were included in the review. Food prescriptions may improve fruit and vegetable consumption and reduce food insecurity (FI). Evidence for impacts on diet-related health outcomes is limited and mixed. The overall quality of included studies was weak. Addressing barriers such as stigma, transportation, and poor nutrition literacy may increase utilization of food prescriptions. Conclusion: Food prescriptions are a promising health care intervention. There is a need for rigorous studies that incorporate larger sample sizes, control groups, and validated assessments of dietary intake, food security, and health.